The rabbit hutch [large type] - Gunty, Tess (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"An online obituary writer. A young mother with a dark secret. A woman waging a solo campaign against rodents -- neighbors, separated only by the thin walls of a low-cost housing complex in the once bustling industrial center of Vacca Vale, Indiana. Welcome to the Rabbit Hutch. Ethereally beautiful and formidably intelligent, Blandine shares her apartment with three teenage boys she neither likes nor understands, all, like her, now aged out of the state foster care system that has repeatedly failed them, all searching for meaning in their lives. Set over one sweltering week in July and culminating in a bizarre act of violence that finally changes everything, The Rabbit Hutch is a savagely beautiful and bitingly funny snapshot of contemporary America, a gorgeous and provocative tale of loneliness and longing, entrapment and, ultimately, freedom"--